'Stylistics will never become boring': An interview with Paul Simpson. (November 2022) - Sorlin, Sandrine
Paul Simpson got his PhD from the University of Ulster in 1984 and took up a post at the University of Nottingham the same year. He has since worked at Queen's University Belfast and Liverpool University, and is currently at the latter institution. He was editor of Language and Literature from 2004 to 2009 after having been assistant editor. In this interview he recalls the influences that got him into stylistics and how he came to find a place for himself in the field. He explains why the international Poetics and Linguistics Association (PALA) is an essential outlet for like-minded individuals who may be in different 'pockets' around the world. He talks about his early interest in sociolinguistics and language variation and what fascinates him about language – the things that are usually dismissed by mainstream linguistics as too messy, problematic or slippery. The creativity of language and the pragmatic ways in which 'language routines' are subverted are at the heart of what interests him as a stylistician. This brings him to come back to the absurdity of speaking of 'literary language' as a separate genre. He comments on his time as editor of Language and Literature, the satisfactions and challenges of the work, the place of the journal in the editorial market and ventures a definition of the broad church of stylistics. Lastly he mentions how stylistics is picking up on new things all the time, going with the tide of new media and approaches, while keeping its momentum at all times and even 'decolonizing' itself in the process.